EVALUACIÓN DEL CRECIMIENTO Y PRODUCCIÓN DE Pleurotus ostreatus SOBRE DIFERENTES RESIDUOS AGROINDUSTRIALES DEL DEPARTAMENTO DE CUNDINAMARCA - Claudia López-Rodríguez; Ricardo Hernández-Corredor; Christian Suárez-Franco; Marta Borrero (Universitas Scientiarum)
The culture of Pleurotus ostreatus was evaluated to determine the best waste on which this mushroom canshow the highest growth and production rates.. The substrates evaluated were agroindustrial wastes of theDepartment of Cundinamarca (dry skin of goldenberries (Physalis), skin of pea pods and maize cobs). Thecontrol substrate was sawdust of oak. The mixtures evaluated were packed in bags of 1 kg containing 78 % ofagroindustrial waste of the volume of substrate mixture . Mixtures were sterilized and inoculated with 30 g ofseeds of Pleurotus ostreatus obtained commercially. Running time of the mycelium, diameter of fruit bodies,number of fruit bodies produced per bag, fresh weight, biological efficiency, and yield were evaluated on eachof the substrates. Finally, the best substrate for the growth and production of Pleurotus ostreatus was the dryskin of goldenberries (Physalis) with a biological efficiency of 76.1% after a total production period of 41days and a yield of 39.03 Kg/m2 with excellent organoleptic characteristics, therefore being an adequate andefficient substrate for cultivating this mushroom.